Off-Site Lime Stabilisation as an Option to Treat Pit Latrine Faecal Sludge for Emergency and Existing On-Site Sanitation Systems. (26th May 2016) - Greya, Wilson; Thole, Bernard; Anderson, Catherine; Kamwani, Flavius; Spit, Jan; Mamani, Grover
Abstract : Off-site lime stabilisation for treating faecal sludge was assessed by undertaking small-scale (35 L) and large-scale (600 L) field trials in Blantyre, Malawi. Hydrated lime was dosed to maintain pH 10, pH 10.5, pH 11, pH 11.5, and pH 12 depending on the buffer capacity of the faecal sludge in the four replica small-scale field trials. Significant reduction of E. coli to below the detection limit of 10 4  CFU/100 mL within 1 hour of treatment was reported for pH > 11. Based on the small-scale findings, large-scale field trials were conducted and greater than3   l o g removal of E. coli was observed under pH 12 conditions. Therefore, based on the study, off-site lime stabilisation by dosing lime in the range of 10–35% w/w (dry solid basis), depending on the buffer capacity and solids content of the sludge to maintain pH > 11, can be used to sanitise faecal sludge during emergencies, as well as for existing on-site sanitation systems.